Arbuscular mycorrhizal fungi enhance soil nutrient cycling by regulating soil bacterial community structures in mango orchards with different soil fertility rates - Han, Yuling; Yuan, Guoyin; Yang, Xiaolong; Fang, Longfa; Liang, Yu; Zhou, Baoyuan; Wei, Zhiyuan (Frontiers in Microbiology, 2025)
Arbuscular mycorrhizal fungi (AMF) substantially enhance soil fertility and are widely recognized as one of the most extensively researched biological inoculants. However, the effects of AMF on soil nutrient availability in mango orchards, along with the physiological processes regulating this availability under varying soil fertility conditions, remain poorly understood. To address this research gap, experiments were conducted with two soil types (soil from mango orchards co-cultivated with butterfly pea plants for 5 years) and a control (no butterfly pea plants) and two mycorrhizal inoculations (+AMF and –AMF). Rhizophagus irregularis was used as the mycorrhizal inoculum. These experiments examined the physicochemical properties, microbial community composition, and metabolic profiles in mango orchard soils by integrating high-throughput sequencing with soil metabolomics. In nutrient-poor soils, the introduction of AMF enhanced the occurrence of specific bacterial species and elevated the richness and diversity of the soil bacterial community. This enhancement subsequently increased the activities of soil enzymes such as cellulase, β-glucosidase, chitinase, and nitrate reductase in mycorrhizosphere soil, leading to improved soil pH, and increases in soil microbial biomass carbon (MBC), ammonium nitrogen (NH4+-N), nitrate nitrogen (NO3−-N), available potassium (K), and available phosphorus (P). Furthermore, alterations in soil properties and metabolites restructured the soil microbial community, with pH and MBC emerging as the key factors shaping bacterial distribution within mycorrhizosphere soil co-occurrence networks. In contrast, the effects of AMF on soil nutrient availability were weaker in high-fertility soils. We conclude that AMF enhance soil nutrient availability in mango orchards by regulating soil bacterial community structures, particularly in low-fertility soils.